Experimenting or Iterating? Exploring Entrepreneurial Retailers' Digital Business Activities through Visual Data Generation - Daniel Nauck, Martin Nowak and Michael Herzog (My University, 2024)
Scholars and policymakers have discussed the emphasis on entrepreneurial growth, especially the importance of cooperation with local and regional stakeholders (e.g. local politics, social or innovation networks, or collaboration with regional universities) to gain inner-city economics resilience and to attract owner-managed retail (OMR) and support entrepreneurial SMEs. We aim to contribute to the discussion by adding an entrepreneurial learning perspective, using insights from an exploratory case study research project, which examined efforts made by entrepreneurial retailers in terms of digitalization during the COVID-19 pandemic through the support of their social network. In doing so, we are introducing and discussing the use of visual data collection within an ego-centered qualitative network analysis (ENA) framework, introducing the method in an entrepreneurship and business management research context.
Keywords: Entrepreneurship; Digital business; Retail; Ego-centred network analysis